Variability of the condylar process of human mandible - Otocki, Piotr; Porowski, Leszek; Bruska, Małgorzata (Anthropological Review, 1978)
Material for this study comprised 187 Barly Medieval skulls excavated at Ostrow Lednicki. The materiai has been broken down into four groups with respect to sex and age (Adultus, Maturus). Student's t-test has not revealed significant intergroup differences of arithmetic means of indices describing shape and height of the condvlar process and height of the articular tubercle of the temporal bone. Similarly, no significant differences were found with respect to absolute dimensions oi the process in Adultus and Maturus groups. Asymmetry of examined characters is insignificant too. Only significant differences found are those resulting from sexual dimorphism in size of bones, Correlation coefficients obtained for relations of: height, surface area and shape index of the process to the height of the articular tubercle proved to be insignificantly different from zero, It has been shown that three basic forms of the shape of condvlar process can be distinguished.